Bioassay-guided isolation and mechanistic action of anti-inflammatory agents from Clerodendrum inerme leaves. (13th May 2015) - Srisook, Klaokwan; Srisook, Ekaruth; Nachaiyo, Wenuka; Chan-In, Mingkwan; Thongbai, Jitra; Wongyoo, Karnjanapa; Chawsuanthong, Sasithorn; Wannasri, Kanita; Intasuwan, Sudarat; Watcharanawee, Kingkan
Abstract: Ethnopharmacological relevance: The leaves of Clerodendrum inerme (L.) Gaertn. have commonly been used in Thai traditional medicine for treatment of inflammatory diseases. However, the bioactive compounds responsible for the anti-inflammatory effect of leaves have not been yet determined. The objective of the present study was to isolate these bioactive compounds by bioassay-guided isolation technique and to determine the mode of action of isolated compounds in LPS-induced macrophages. Materials and methods: Anti-inflammatory effect of various fractions (hexane, ethyl acetate and water) of ethanol extract of C. inerme leaves was determined from the production of nitric oxide (NO) in RAW 264.7 macrophage stimulated with LPS. The mRNA and protein levels were determined also by real-time reverse transcription-polymerase chain reaction and western blot analysis, respectively. Leaf bioactive compounds were isolated by bioassay-guided fractionation technique using column chromatography. Results: The ethyl acetate fraction (EA) among solvent extracts provided the most potent inhibitory activity on NO production. Also, EA reduced the mRNA and protein expressions of inducible nitric oxide synthase (iNOS) in LPS-stimulated macrophages. Three known flavones, acacetin (1 ), hispidulin (2 ) and diosmetin (3 ), were isolated based on inhibition of NO production. Furthermore, hispidulin also inhibited PGE2 production as well as iNOS and cyclooxygenase-2 expressions via the blockade of NF-κB DNA-binding activity and JNKway. Conclusions: Our results found acacetin (1 ), hispidulin (2 ) and diosmetin (3 ), were responsible for the anti-inflammatory properties of C. inerme leaves. We provide scientific evidence to support the usefulness of C. inerme leaves in traditional medicine for the treatment of inflammation-related diseases. Graphical abstract: